Parents' motivation in Delivering their children to study at Madrasah Diniyah Awaliyah Alkhairaat - Saripah Saripah; Sagaf S. Pettalongi; Ahmad Syahid (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2021)
The aim of this study is to find out parents’ motivation in delivering their children to study in Madrasah Diniyah Awaliyah Alkhairat Tomado Sigi regency. This study used qualitative method in which the data was gathered through direct observation, in-depth interview with students’ parents, and written material. The result of the study shows that the motivation of parents in delivering their children to Madrasah Diniyah Awaliyah School is to increase students’ achievement knowledge and religious values. Parents were not only expecting their children to succeed in general subject but also in Islamic religion knowledge and values.